Combinatorial Library Methods and Protocols - English, Lisa Bellavance (Humana Press, 2002)
Recent advances in com- natorial library synthesis, purification, and analysis techniques are not only increasing the numbers of compounds that can be tested against each specific genomic target, but are also speeding and improving the overall processes of lead discovery and optimization.